Prospect . 4. - de Gele Zaal, Gent (Gent : Noordstarfonds vzw, 1987)
Venlet, Richard ; Peters, Willy ; Schepers, Marc ; Grossen, Luc ; Boes, Dirk
Prospect . 4, De Gele Zaal, Gent, 9.5 - 21.6.1987
boek